THE PROBLEM OF EMOTIONAL RESPONSE TO STRESSFUL SITUATIONS UNDER THE CONDITIONS OF MARITAL STATE - Hruzynska, Iryna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to the problem of ensuring an individual's optimal response to stressors associated with martial law. The relevance of this problem is determined precisely by the insufficient development of issues of psychological protection of citizens of Ukraine who suffer from the negative psycho-emotional impact caused by the war. The purpose of the article is the theoretical analysis and empirical determination of the features of the emotional response to stressful situations in the conditions of martial law and the substantiation of the psychological conditions for optimizing the psycho-emotional state of the individual in the conditions of stressful situations associated with limited resources. The tasks of the research include working out the categorical and conceptual foundations of the psychological problems of emotional response to stressful situations related to martial law, the analysis of the relevant scientific and theoretical base developed by researchers in the field of stressology, the definition of the stages of martial law, the specificity of which determines the peculiarities of the psycho-emotional response of an individual, empirical identification of features of emotional response to stressful situations at each of the stages of martial law and substantiation of psychological conditions and practical methods of optimizing the psycho-emotional state of the individual. The results: taking into account the specifics of the psycho-emotional load of student youth on different days of the war, the stages of martial law were differentiated as the first day of the war, preparation for evacuation, evacuation, placement in the place of evacuation, preparation for returning home and returning home. Summarizing the results of the author's questionnaire, the peculiarities of the personal response of students at each of the above-mentioned stages were determined and the factors of stress development were determined. A noticeable instability of the mental state of students was revealed, which leads to rigidity, inability to withstand stressful situations, excitability, the occurrence of cognitive difficulties, a constant feeling of fear, anxiety, and increasing emotional tension. Conclusions. Summarizing the results of the study, it was determined that the external stress factor - the state of war causes negative anxiety-depressive emotions in students, which affect the decrease in the level of stress resistance. In order to increase the resource of stress resistance, reduce the influence of negative psychogenic factors and optimize the psycho-emotional state of a person in an emergency situation related to the state of war, it is proposed to use methods aimed at improving mobilization protective reactions, increasing the body's resistance to stressors, increasing adaptation reserves, revealing own unique creative potential, overcoming emotional destructive mood